Modelling The Relationship Between Psychological Climate Factors And Organizational Profitability In Construction Organization - Mosahab, Rahim (2018)
The study developed and tested a model of mediation association that explains the relationship between psychological climate factors and organization profitability. The model was tested in the context of G7 group of construction companies’ professional employees in Penang State, Malaysia. Upon completion of the pilot study, with estimating a response rate of 25%, a number of 980 questionnaires were distributed to 49 participating construction companies to be completed. A total of 441 (45%) questionnaires were collected. The usable responses were 294, implying a response rate of 30%.